Residue-Specific Message Encoding in CD40-Ligand - Aditya Yashwant Sarode; Mukesh Kumar Jha; Shubhranshu Zutshi; Soumya Kanti Ghosh; Hima Mahor; Uddipan Sarma; Bhaskar Saha (iScience, 2020)
Summary: CD40-Ligand (CD40L)-CD40 interaction regulates immune responses against pathogens, autoantigens, and tumor and transplantation antigens. Single amino acid mutations within the 115–155 amino acids stretch, which is responsible for CD40L functions, result in XIgM syndrome. We hypothesize that each of these amino acids of CD40L encodes specific message that, when decoded by CD40 signaling, induces a specific profile of functions. We observed that every single substitution in the XIgM-related amino acids in the 115–155 41-mer peptide in CD40L selectively altered CD40 signaling and effector functions—cytokine productions, HMGCoA reductase, ceramide synthase, inducible nitric oxide synthase and arginase expression, survival of B cells, and control of Leishmania infection and anti-leishmanial T cell response—suggesting residue-specific encoding of a distinct set of messages that collectively define CD40L pleiotropy, serve as a target for engineering the ligand to generate superagonists as immunotherapeutic, and implicate the evolutionary diversification of functions among the ligands in a protein superfamily.